1985
DOI: 10.1016/0378-4320(85)90065-x
|View full text |Cite
|
Sign up to set email alerts
|

Parturition difficulties in sheep

Abstract: Anim. Reprod. Sci., 9: 365--374.The incidence of difficult parturition was recorded in Texel Sheep lambs (224), Milk Sheep lambs (273) and various crossbreeds (1043) in ten spring lambing seasons. At lambing time the ewes were under 24-hour observation.Difficult parturition is defined as necessity for obstetrical assistance as a result of failure of expulsion or progress within a given time limit.The course of parturition was recorded on a standard protocol. Shortly after parturition ewes and lambs were weighe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
7
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 12 publications
4
7
0
Order By: Relevance
“…In this study, the differences in the proportion of ewe dystocia caused by oversized lambs between the sire breeds was in line with their respective differences in lamb birth weight. However, this study also found a significant effect of sire breed on ewe dystocia caused by lamb malpresentation, independent of birth weight, which is in agreement with Grommers et al (1985). The slightly higher incidence of malpresentations in ewes mated to Swaledale sires could be explained by a larger litter size.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, the differences in the proportion of ewe dystocia caused by oversized lambs between the sire breeds was in line with their respective differences in lamb birth weight. However, this study also found a significant effect of sire breed on ewe dystocia caused by lamb malpresentation, independent of birth weight, which is in agreement with Grommers et al (1985). The slightly higher incidence of malpresentations in ewes mated to Swaledale sires could be explained by a larger litter size.…”
Section: Discussionsupporting
confidence: 86%
“…The age of ewe also had a small effect on the incidence of ewe dystocia, with younger ewes having higher risk of dystocia. This is consistent with the inexperience at lambing of young (primiparous) ewes and their disadvantage when delivering lambs that are too large for them (Woolliams et al, 1983;Grommers et al, 1985). Ewe dystocia, as expected (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…This is the first study to report the effect of EP and MP nutrition on the incidence of dystocia. There is a well-established link between birth weight and the incidence of dystocia in ewes (Grommers et al, 1985;Dwyer et al, 1996). However, dystocia is not related simply to birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…However, dystocia is not related simply to birth weight. Grommers et al (1985) identified birth presentation as the most significant factor influencing the incidence of parturition difficulty. Normal birth presentations in the current study most certainly influenced the amount of assistance required at lambing, but were not directly affected by plane of nutrition in EP.…”
Section: Discussionmentioning
confidence: 99%
“…Lamb birth weight is related to litter size, with singletons more likely to be too heavy, and lambs born in multiple litters more likely to be too light, to meet this optimum. The genetic basis to lambing ease was realised when breed differences in the occurrence of lambing difficulties were first reported (Grommers, 1985). The aim of this study was to evaluate the genetic component of lambing difficulty in Scottish Blackface sheep and to explore key environmental components affecting the occurrence of dystocia in this population.…”
mentioning
confidence: 99%